PELATIHAN SISTEM AKUNTANSI KOPERASI DI DESA PETIGA, KECAMATAN MARGA, KABUPATEN TABANAN - Darsana, I Made (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2023)
The purpose of implementing this activity is to increase knowledge and skills for administrators, cooperative business managers with accounting principles so that cooperative finances run in an orderly manner and understand the general provisions for preparing financial reports. This activity is certainly very beneficial for cooperatives, considering that in the midst of intense competition, cooperatives must be able to compete in a healthy and professional manner to achieve a high level of efficiency. The Savings and Loans Cooperative in Petiga Village, Marga Sub-District, Tabanan, as an economic organization engaged in raising funds for the community, must be able to compete professionally with other financial institutions. In order to achieve efficient, effective, business-worthy performance and at the same time be able to obtain an optimal level of profit or calculation of business results, it is necessary to be supported by strong human resources, an orderly administration system, consistent accounting policies and proper accounting processes.